1994
DOI: 10.2307/3578912
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effect of Lead-212 Localized in the Nucleus of Mammalian Cells: Role of Recoil Energy in the Radiotoxicity of Internal Alpha-Particle Emitters

Abstract: The radiochemical dipyrrolidinedithiocarbamato-212 Pb(II) [ 212 Pb(PDC) 2 ] is synthesized and its effects on colony formation in cultured Chinese hamster V79 cells are investigated. The cellular uptake, biological retention, subcellular distribution and cytotoxicity of the radiocompound are determined. The 212 Pb is taken up quickly by the cells, reaching saturation levels in 1.25 h. When the cells are washed, the intracellular activity is retained with a biological half-life of 11.6 h. Gamma-ray spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…However, the 0.1% cutoff was implemented neither for the spectrum of b particles nor for Auger electrons. The recoil energy of the residual daughter after a decay was not included because experiments indicate that this energy is not biologically relevant (36). The "b Average Energy Spectrum" option provides the radiation data contained on the compact disk that accompanies the second edition of MIRD: Radionuclide Data and Decay Schemes (37).…”
Section: Methodsmentioning
confidence: 99%
“…However, the 0.1% cutoff was implemented neither for the spectrum of b particles nor for Auger electrons. The recoil energy of the residual daughter after a decay was not included because experiments indicate that this energy is not biologically relevant (36). The "b Average Energy Spectrum" option provides the radiation data contained on the compact disk that accompanies the second edition of MIRD: Radionuclide Data and Decay Schemes (37).…”
Section: Methodsmentioning
confidence: 99%
“…These were both assigned a value of 0.64 Gy which corresponds to the experimental dose required to achieve 37% survival ( D 37 ) when 100% of the cells were labeled with 210 Po-citrate, an emitter of 5.3 MeV alpha-particles (Neti and Howell 2007). The assumption of D 37,self = D 37,cross derives from our previous studies which showed equivalent RBE values for intranuclearly and cytoplasmically localized alpha emitters (Azure et al 1994). A Monte Carlo method was used to determine whether a given target cell suffered radiation-induced cell death (Rajon et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Although there is considerable experimental data on the biological effects of α particles in vitro (35)(36)(37)(38)(39)(40)(41)(42), there is a dearth of in vivo data that systematically explore the dependence of RBE on the energy of α particles emitted by incorporated radionuclides. In this work, an empirical RBE-E α relationship was obtained using spermatogenesis in mouse testes as the experimental model and survival as the biological end point.…”
Section: Discussionmentioning
confidence: 99%